Pembaruan akad Nikah: Internalisasi Hukum Islam dalam Tradisi Lokal - Musonnif, Ahmad; Muazza, Sahira Rif’anil (Sakina: Journal of Family Studies, 2024)
Renewal of marriage is one of the phenomena that exists in Muslim society in Indonesia. This phenomenon arises because of several factors, including poor conditions in the family, traditions, and so on. The investigation focused on the practice of marriage renewal in the village of Kemasantani, performing interpretations of their behavior and a thorough analysis of the views of the public and scholars about marriage. The methods used are interviews and literary studies. The results of the research show that the view of the Java people who practise the renewal of marriage is based on the belief that marriage was a worship that could be used as a means of prayer to God to obtain desire. First, scholars who consider marriage renewal can cancel the previous contract because it is a recognition (iqrar) of divorce. Second, scholars who consider that the renewal of marriage does not damage (faskh) the previous contract is analogous to the practice of the companions repeating bay'at by Companion to the Prophet PBUH. In addition, marriage renewal is informing (ikhbar), strengthening (ta'kid), embellishing (tajammul), and prudence (ikhtiyath).